2021
DOI: 10.1111/ane.13433
|View full text |Cite
|
Sign up to set email alerts
|

Electrodiagnostic findings in patients with non‐COVID‐19‐ and COVID‐19‐related acute respiratory distress syndrome

Abstract: Background Critical illness polyneuropathy and myopathy (CIPNM) is a frequent neurological manifestation in patients with acute respiratory distress syndrome (ARDS) from coronavirus disease 2019 (COVID‐19) infection. CIPNM diagnosis is usually limited to clinical evaluation. We compared patients with ARDS from COVID‐19 and other aetiologies, in whom a neurophysiological evaluation for the detection of CIPNM was performed. The aim was to determine if there were any differences between these two groups in freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Obwohl es intensivmedizinisch durch eine Coronavirus-disease-19(COVID-19)-Erkrankung häufig zu prolongierten Verläufen mit einer langen Beatmungsnotwendigkeit kommt, ist die Critical-illness-Polyneuropathie-Myopathie (CIPNM) nur unzureichend in diesem Patientenkollektiv untersucht. Patienten mit einem „acute respiratory distress syndrome“ (ARDS) allein ( n = 21) und ARDS aufgrund einer COVID-19-Infektion ( n = 23) wiesen keine unterschiedliche Inzidenz der CIPNM in dieser neurophysiologisch gut aufgearbeiteten Kohorte auf [ 23 ]. In einer anderen Studie wurden neurophysiologische Untersuchungen und Serumbiomarker verglichen zwischen COVID-Patienten, die keine oder eine CIPNM entwickelten [ 8 ].…”
Section: Neues Zur Critical-illness-polyneuropathie-myopathie Nach Co...unclassified
“…Obwohl es intensivmedizinisch durch eine Coronavirus-disease-19(COVID-19)-Erkrankung häufig zu prolongierten Verläufen mit einer langen Beatmungsnotwendigkeit kommt, ist die Critical-illness-Polyneuropathie-Myopathie (CIPNM) nur unzureichend in diesem Patientenkollektiv untersucht. Patienten mit einem „acute respiratory distress syndrome“ (ARDS) allein ( n = 21) und ARDS aufgrund einer COVID-19-Infektion ( n = 23) wiesen keine unterschiedliche Inzidenz der CIPNM in dieser neurophysiologisch gut aufgearbeiteten Kohorte auf [ 23 ]. In einer anderen Studie wurden neurophysiologische Untersuchungen und Serumbiomarker verglichen zwischen COVID-Patienten, die keine oder eine CIPNM entwickelten [ 8 ].…”
Section: Neues Zur Critical-illness-polyneuropathie-myopathie Nach Co...unclassified
“…Regarding ICU complications, there were no differences in the rates of muscular weakness, cardiovascular and abdominal complications, data consistent with the literature. ( 40 )…”
Section: Discussionmentioning
confidence: 99%
“…Concerning neuromuscular disorders, some neurophysiological parameters, such as nerve conduction (electroneurography-ENG) and electromyography (EMG), for the evaluation of spontaneous activity, have been used for CIPNM detection in critically ill patients [13,21,47]. The authors showed that the presence of CIPNM may prolong recovery time in IRUs, worsen the final outcome and increase the cost of hospitalisation [54,55].…”
Section: Protracted Phasementioning
confidence: 99%